Deep colour-magnitude diagrams of LMC field stars imaged with HST - Castro, Rodrigo (2001)
We present deep photometry V < ~26 in V and I bands obtained with the Wide Field and Planetary Camera 2 on board the Hubble Space Telescope for 7 fields ~5◦ away from the Large Magellanic Cloud centre. The fields contain, typically, 2000 stars each. Isochrones were fitted to the colour–magnitude diagrams in order to identify different star populations in these fields. An old population (t > 10 Gyr) has been found in all fields. Some events of enhanced star formation, with ages between 2 and 4 Gyr, were identified in the fields localized in the north to north-west regions. Luminosity functions of low-mass stars were also obtained for all fields. Kolmogorov Smirnov test results suggest differences smaller than 30 per cent in the mixture of stellar populations contributing to the fields. Finally, density profiles were derived for old and intermediate-age stars. The former shows a slightly steeper decline than the latter.